IAU South-West and Central Asian Regional Offce of Astronomy for Development - Mickaelian, A. M.; Farmanyan, S. V.; Mikayelyan, G. A.
The International Astronomical Union (IAU) announced its Strategic Plan on Astronomy for Development in 2009, during the International Year of Astronomy (IYA). One of its main components was the creation of the Offce of Astronomy for Development (OAD) and corresponding Regional Offces (ROADs) for implementation and coordination of its aims. The OAD was created in Cape Town, South Africa and later on ROADs were created in 11 regions. Since 2015, Armenia hosts one of them, IAU South West Asian (SWA), later renamed to South West and Central Asian (SWCA) ROAD. At present, already 6 countries have offcially joined (Armenia, Georgia, Iran, Kazakhstan, Tajikistan, and Turkey), but the Offce serves for a rather broad region, from Eastern Europe to Central Asia. Armenia's geographical location and its historical role in astronomy (both for well-known archaeoastronomical heritage and the presence of the famous Byurakan Astrophysical Observatory (BAO) founded by Viktor Ambartsumian in 1946) serve as a link between Europe and Eastern Partnership countries, Middle East and Asia in general. We run activities in 3 directions, Task Forces (TF): TF1 Universities and Research, TF2 Children and Schools and TF3 Public Outreach. We present our projects and all other accomplishments and discuss the role of our ROAD in maintaining contacts and development of astronomy in the region, as well as contacts between Europe and the Eastern Partnership countries. Most up-to-date information about the IAU SWCA ROAD is available on its webpage at http://iau-swa-road.aras.am/eng/index.php.
Keywords: Astronomy